2022
DOI: 10.3390/v14030510
|View full text |Cite
|
Sign up to set email alerts
|

Previous Infection with SARS-CoV-2 Correlates with Increased Protective Humoral Responses after a Single Dose of an Inactivated COVID-19 Vaccine

Abstract: Previous studies have indicated that antibody responses can be robustly induced after the vaccination in individuals previously infected by SARS-CoV-2. To evaluate anti-SARS-CoV-2 humoral responses in vaccinated individuals with or without a previous history of COVID-19, we compared levels of anti-SARS-CoV-2 antibodies in the sera from 21 vaccinees, including COVID-19-recovered or -naïve individuals in different times, before and after immunization with an inactivated COVID-19 vaccine. Anti-SARS-CoV-2-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Future studies could seek to identify vaccine-induced anti-SARS-CoV-2 S antibodies in urine, particularly because most approved vaccines use SARS-CoV-2 S protein to elicit protective immunity. Anti-SARS-CoV-2 S antibodies elicited after COVID-19 and/or immunization with an inactivated vaccine have been identified by serumbased ELISA, using the same rSARS-CoV-2 Euk1-S1 protein as used in our study 28 , indicating the potential of identifying vaccine-generated antibodies by our urine-based ELISA. It is worth noting that the antibodies were identified in samples collected in 2020 and as the S protein continues to mutate, future studies are probably still needed to establish assay sensitivity in patients infected with SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Future studies could seek to identify vaccine-induced anti-SARS-CoV-2 S antibodies in urine, particularly because most approved vaccines use SARS-CoV-2 S protein to elicit protective immunity. Anti-SARS-CoV-2 S antibodies elicited after COVID-19 and/or immunization with an inactivated vaccine have been identified by serumbased ELISA, using the same rSARS-CoV-2 Euk1-S1 protein as used in our study 28 , indicating the potential of identifying vaccine-generated antibodies by our urine-based ELISA. It is worth noting that the antibodies were identified in samples collected in 2020 and as the S protein continues to mutate, future studies are probably still needed to establish assay sensitivity in patients infected with SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 76%
“…We adapted an in-house urine-based ELISA protocol using rSARS-CoV-2 S proteins to evaluate the presence of anti-SARS-CoV-2 S antibodies in urine samples collected at different days Post Symptom Onset (PSO) from previously confirmed qRT-PCR positive patients. We used the well-established serum-based ELISA 28 to compare efficiency. We evaluated the immunodiagnostic efficacy for COVID-19 of three rSARS-CoV-2 S proteins, one expressed in a eukaryotic system, Euk1-S1, and two expressed in a prokaryotic system, Prok1-S1 and Prok2-S1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies show that SARS-CoV-2 infection induces the production of neutralizing antibodies in most infected patients [ 31 , 32 , 33 ]. We studied the effect of prior vaccination with Sputnik V on the production of IgG, as well as serum neutralizing activity, after SARS-CoV-2 Omicron infection.…”
Section: Resultsmentioning
confidence: 99%
“…A single dose of vaccine elicited higher memory T and B-cell responses in previously infected individuals ( 41 ). Due to the existence of immune memory, previously infected individuals produce more rapid and lasting cellular and humoral immunity after vaccination ( 42 , 43 ). Further research found that there were significantly higher levels of antibodies in fully vaccinated individuals with natural immunity than in fully vaccinated individuals without prior infection.…”
Section: Discussionmentioning
confidence: 99%